2017
DOI: 10.1186/s13073-017-0481-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Wiskott–Aldrich syndrome protein co-regulates T cell factor 1-mediated transcription in T cells

Abstract: BackgroundThe Wiskott–Aldrich syndrome protein (WASp) family of actin-nucleating factors are present in the cytoplasm and in the nucleus. The role of nuclear WASp for T cell development remains incompletely defined.MethodsWe performed WASp chromatin immunoprecipitation and deep sequencing (ChIP-seq) in thymocytes and spleen CD4+ T cells.ResultsWASp was enriched at genic and intergenic regions and associated with the transcription start sites of protein-coding genes. Thymocytes and spleen CD4+ T cells showed 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 78 publications
(91 reference statements)
0
22
0
Order By: Relevance
“…Recent research has shown that WASP directly interacts with TCF-1 in the nucleus. 11 TCF-1 is a transcriptional factor that is homologous to LEF-1 and expressed in B cells. 9 To examine whether WASP interacted with LEF-1 in B cells, WT B cells were stimulated with sAg, and confocal microscopy and immunoprecipitation assays were performed for WASP and (Fig 5, E) and the MFI of BCR (Fig 5, F), actin (Fig 5, G), and pY ( Fig 5, H) in the contact zone from 3 independent experiments.…”
Section: Absence Of Dock2 Reduces Accumulation Of Bcr Clustering Posmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that WASP directly interacts with TCF-1 in the nucleus. 11 TCF-1 is a transcriptional factor that is homologous to LEF-1 and expressed in B cells. 9 To examine whether WASP interacted with LEF-1 in B cells, WT B cells were stimulated with sAg, and confocal microscopy and immunoprecipitation assays were performed for WASP and (Fig 5, E) and the MFI of BCR (Fig 5, F), actin (Fig 5, G), and pY ( Fig 5, H) in the contact zone from 3 independent experiments.…”
Section: Absence Of Dock2 Reduces Accumulation Of Bcr Clustering Posmentioning
confidence: 99%
“…TCF-1 target genes are enriched in Wiskott-Aldrich syndrome protein (WASP)-deficient B cells, and WASP interacts with TCF-1 in the nucleus. 11 Recently, we found WASP protein expression is reduced in dedicator of cytokinesis protein 8-deficient B cells. 12 Loss of WASP, DOCK2, and dedicator of cytokinesis protein 8 all lead to a reduction in numbers of marginal zone (MZ) B cells.…”
mentioning
confidence: 97%
“…Moreover, its interaction with the protein characteristic for DSBs (γH2AX) was also confirmed [ 87 ]. WASP may also be involved in the regulation of RNA polymerase II activity [ 88 ]. Additionally, the correlation between WASP and the p53/p21 signaling pathway also plays an important role in carcinogenesis [ 89 ], whereas the relationship between N-WASP and oncogenic KRas was observed in pancreatic ductal adenocarcinoma [ 90 ].…”
Section: Actin and Abps In Carcinogenesismentioning
confidence: 99%
“…In this regard, chromatin immunoprecipitation (ChIP) experiments have revealed an association of WASp with TbxT1 genes (124,125). Moreover, RNA sequencing analysis revealed different genetic regulation in the presence and absence of WASp (126). As WASp lacks DNA binding motifs, it is possible that these effects are in part mediated via its actin polymerization activity.…”
Section: Genomic Stabilitymentioning
confidence: 99%
“…Emergence of tools to specifically study actin filaments in the nucleus using specific reporters with nuclear localization signals as well as the presence of filament regulators such as WASp and Arp2/3 in the nucleus have reignited interest in this field. A role for nuclear actin filaments has been described in (1) homologous repair of heterochromatic double strand breaks in Drosophila oocyte where actin nucleation via Arp2/3 generate tracks for myosins to transport heterochromatic double-strand break to the nuclear lamina ( 128 , 129 ), (2) regulating gene expression following serum starvation via N-WASp/RNA polymerase II interactions ( 130 ) and (3) in regulating the expression of key cytokines downstream of T cell receptor engagement ( 126 , 131 ).…”
Section: Malignancies In Pid Patientsmentioning
confidence: 99%